SOCIOCULTURAL CHANGE OF SCIENTIFIC COGNITION - Скиба, О. П. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article deals with the research of sociocultural factors influence on the process of scientific cognition.